Cellulose-based aerogels from sugarcane bagasse for oil spill-cleaning and heat insulation applications. (15th January 2020) - Thai, Quoc Ba; Nguyen, Son Truong; Ho, Duong Khanh; Tran, Tuan Du; Huynh, Dat Minh; Do, Nga H.N.; Luu, Thao Phuong; Le, Phung K.; Le, Duyen K.; Phan-Thien, Nhan; Duong, Hai M.
Graphical abstract: Highlights: A green and cost-effective method to convert sugarcane bagasse into aerogel has been developed. Sugarcane bagasse aerogel is a promising candidate for heat insulation applications. Sugarcane bagasse aerogel is a promising candidate for oil-spill cleaning applications. Sugarcane bagasse aerogel is highly flexible, and can be bent without breaking. Abstract: A promising and economic material for various applications, such as thermal insulation in construction building and oil clean-up in marine ecosystems, is successfully developed from the by-product of the sugarcane industry. Biodegradable sugarcane bagasse aerogels are produced using polyvinyl alcohol (PVA) binder, followed by a freeze-drying method. This environmental-friendly recycled aerogel has an ultra-low density ([0.016-0.112] g/cm 3 ), a high porosity ([91.9–98.9]%), and a very low thermal conductivity ([0.031-0.042] W/mK). Its superhydrophobicity properties and its maximum oil absorption capacity (up to 25 g/g) are measured after coating aerogel samples with methyltrimethoxysilane (MTMS). The biodegradable aerogel has a Young's modulus of 88 K Pa and can be bent without breaking, demonstrating its high flexibility.